Analysis of the association between polymorphism in DHFR and SLC19A1 genes, clinical factors and methotrexate-related side effects in rheumatoid arthritis patients from HUSM, Kelantan - Zahari, Mohamad Syazwan (2018)
Methotrexate (MTX) is folic acid antagonist that widely used for treatment of rheumatoid arthritis (RA) nowadays. Despite its proven efficacy in RA patients, the occurrence of adverse effects is a major reason for drug discontinuation. Generally, more than 30% of patients on MTX are susceptible to risk of MTX-related adverse effects (AEs) in which 19% of them had discontinued the drug. In clinical setting, it is currently challenging to predict which patients on MTX are possibly developing drug toxicity. Most studies speculate demographic characteristics and clinical factors are associated with risk of MTX-related AEs. Besides that, the genetic polymorphisms in the folate pathway are also implicated in MTX outcome. Two single nucleotide polymorphisms (SNPs) in dihydrofolate reductase (DHFR) (i.e; rs12517451) and solute carrier family 19 folate transporter member 1, SLC19A1 (i.e: rs1050266) genes were reported as promising predictive genetic markers for MTX toxicity. Until now, no genetic association study among Malaysian population has explored the influence of both SNPs on MTX toxicity. Therefore, we aim to study the association of SLC19A1 rs1051266 and DHFR rs12517451 variants, together with other clinical factors on MTX-related AEs among RA patients from HUSM, Kelantan. This is a case-control study, and involves 72 RA patients, 27 patients were assigned as cases and 45 patients were classified as control. All information regarding demographics and clinical characteristics of patients were obtained through examination of patient’s medical records. The genotyping of selected archived DNA samples of RA samples were performed by using PCR-RFLP (Polymerase Chain Reaction-Restriction Fragment Length Polymorphism) technique and followed by sequencing. The results indicated that, the most frequent MTX toxicity was Gastrointestinal (GI) toxicity (37%), followed by haematological toxicity (29.6%), skin toxicity (18.5%), pulmonary toxicity (14.8%), fatigue (11.1%) and only one patient with elevated liver enzyme level was identified. The results also indicated that there were no difference in demographic variables and clinical factors analysed between cases and controls. Besides that, no significant different in the genotype and allele frequencies for both DHFR rs12517451 and SLC19A1 rs1051266 variant between cases and controls was found suggesting that both SNPs were not associated to the risk of MTX-related AEs. Due to small sample size, our finding warrant further investigation and replication in larger patient cohort and in multicentre trials.